SETTLING BEHAVIOR RELATIONSHIP OF OVERBURDEN MATERIALS X AND Y AT PT XYZ BASED ON ANALYTICAL APPROACH OF PARTICLE SIZE DISTRIBUTION (PSD) CURVE AND IMHOFF CONE METHOD - Larissa Nugraheni, Lisa
The settling behavior of the material becomes a fundamental control in determining the dimensions of the settling pond as a passive erosion control measure. This research is important to understand the relationship between the settling behavior of X and Y overburden materials based on the analytical approach of Particle Size Distribution (PSD) curve and the Imhoff Cone Method test. The data used in this study are secondary PSD data and primary data. The primary data collection method with the Imhoff Cone Method test includes sample preparation, test execution, and sieve analysis of Imhoff test results. The OB X material was classified as silty clay class producing 39.44 grams of bedload material and a final sediment volume of 8.50 ml/L which was constant after 4 hours. While OB Y in the clay class produced 33.14 grams of bedload material and a final sediment volume of 14 ml/L which was constant after 5 hours. The representative diameters of particles deposited in each time interval for both samples were in the fine sand and silt size range. The settling time range of fine sand OB X and OB Y was 2 hour and 0.5 hour while silt was 4 hours and 5 hours. Based on the test results, it is found that the material texture class affects the amount of bed load material, suspended solid concentration, sediment volume, and the time to reach a constant sediment volume. The Imhoff test results can be used as a basis for selecting a representative diameter to represent the overall settling time range of the material rather than looking at the particle size range in the PSD of the overall sample or the PSD of the suspended solid in the Imhoff test. So that there is no overestimate when estimating settling time in designing sedimentation ponds.